الاتصال الداخلي و دوره في ادارة الجودة الشاملة - طيفور خديجة; بن قيط العالية; هويشر مسعود (جامعة عمار ثليجي الاغواط, 2024)
الملخص: بناءً على البحث الذي قمت به، إليك ملخص دراسة عن الاتصال الداخلي ودوره في إدارة الجودة الشاملة تناولت هذه الدراسة دور الاتصال الداخلي في تطبيق إدارة الجودة الشاملة في المنظمات. حيث ركزت على أهمية الاتصال الداخلي كأحد المتطلبات الأساسية لنجاح تطبيق إدارة الجودة الشاملة. أظهرت النتائج أن هناك علاقة إيجابية قوية بين فعالية نظام الاتصال الداخلي في المنظمة وتحقيق أهداف إدارة الجودة الشاملة. فالاتصال الداخلي الفعال يساعد على نشر ثقافة الجودة، وتوفير المعلومات اللازمة لجميع الموظفين، وتشجيع العمل الجماعي وروح الفريق، مما ينعكس إيجابياً على تطبيق ممارسات إدارة الجودة الشاملة. كما أوضحت الدراسة أن من أهم متطلبات الاتصال الداخلي الفعال في إدارة الجودة الشاملة هي: وجود قنوات اتصال متعددة ومفتوحة، تدفق المعلومات بشكل فعال في جميع الاتجاهات، وتوفير التغذية الراجعة المنتظمة بشأن جهود تطبيق الجودة. في الختام، خلصت الدراسة إلى أن تطوير نظام اتصال داخلي فعال يُعد أمراً حيوياً لنجاح تطبيق إدارة الجودة الشاملة في المنظمات. Summary: Based on the research conducted, here is a summary of a study on internal communication and its role in Total Quality Management (TQM): This study addressed the role of internal communication in the application of Total Quality Management (TQM) in organizations. It focused on the importance of internal communication as one of the essential requirements for the successful implementation of TQM. The results showed a strong positive relationship between the effectiveness of the internal communication system in the organization and the achievement of TQM objectives. Effective internal communication helps in spreading a culture of quality, providing necessary information to all employees, and encouraging teamwork and team spirit, which positively reflects on the application of TQM practices. The study also indicated that the most important requirements for effective internal communication in TQM include: the presence of multiple and open communication channels, the effective flow of information in all directions, and the provision of regular feedback regarding quality implementation efforts. In conclusion, the study found that developing an effective internal communication system is crucial for the successful implementation of TQM in organizations.
دراسة ميدانية بالمؤسسة الاقتصادية سونلغاز